Bihār Riyāsatī Qānūn Sāz Isamblī kī ḵẖuṣūṣī kamiṭī, Bihār Riyāsatī Sunnī Vaqf Borḍ kī ḵẖuṣūṣī rīporṭ, 1994 : peshkash kī tārīḵẖ: 23 Mārc 1994 (Bihār Riyāsatī Sunnī Vaqf Borḍ, 1994)
Special report of the Bihar State Sunni Waqf Board presented in the Bihar Legislative Assembly on 23 March 1994.